Optimalisasi Penugasan Normal Menggunakan Metode Hungarian Maksimisasi: (Studi Kasus: CV. Surya Pelangi) - Pesta Gultom; Anggi Br Tarigan; Sartika Mayang Sari; Chairuna Chairuna; Panglima Martin Sitepu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The assignment problem discusses the problem of creating maximum sales, CV Surya Pelangi assigns its selected employees to enter the target market. CV Surya Pelangi has problems allocating its employees to the target market that has been determined. Before allocating its employees, CV Surya Pelangi has conducted training first. The income data of each employee in these markets is in (thousands) during training, therefore it is necessary to solve the employee allocation problem. The method used in this study is the Hungarian Method, with a focus on the maximization approach. The Hungarian method is known to be effective in solving assignment problems where there are similarities in the number of employees and allocations, and the goal is to optimize the allocation. In this case, maximization means finding a combination of assignments that produce the highest total profit value.